Healthcare Delivery among Yoruba Bonesetters in Southwest Nigeria and the Need for Collaboration with Orthodox Orthopedic Healthcare Services: A Mixed Method Study - Soladoye S. Asa; Matthew O. Ilori; Lawrence A. Akinyoola (Yoruba Studies Review)
This study covers three purposively chosen states; Ogun, Ondo, and Oyo, in southwestern Nigeria. Primary data were collected using three sets of questionnaires. The respondent-driven sampling (RDS) technique was employed in selecting the respondents for the study. A total of 69 traditional bonesetters (TBS), 130 TBS patients, and 15 orthopedic surgeons were interviewed. The study reveals that majority (91.2%) of the TBS in the study area claimed that they had received an average of 11 patients from orthodox hospitals in the year preceding the survey while about 9.0% of the respondents reported that 78 Soladoye S. Asa, Matthew O. Ilori, and Lawrence A. Akinyoola they had on the average advised 6 patients per year to relocate to orthodox hospitals. The study also reveals the views of TBS areas of need from government to include recognition (93.7%) and integration into the country’s health system (63.5%). A majority (93.3%) of the orthopedic surgeons reported having received patients from TBS, and each surgeon had received, on average, 37 patients per year. All the orthopedic surgeons surveyed believed that TBS lacked knowledge in the management of bone injuries, apart from setting bones. Other issues considered critical by the doctors in the management of fractures by TBS included lack of training in the biology of bones (86.7%) and inability to refer cases to modern health facilities (73.3%). The proportion of orthopedic surgeons who had ever thought of a possible interaction between TBS and orthopedic surgeons was 80.0% while 86.7% would advise the establishment of such interaction. Furthermore, the study reveals that more than half (54.6%) of TBS patients made a TBS clinic their first choice for treatment. The paper concludes that integration will go a long way to improving the health of the population, thereby significantly reducing deaths or disability-adjusted life years (DALYs) lost.